Fazlur Rahman’s Thought on Islamic Education: Its Relevance to the Concept of Meaningful Learning - Alfi Noer Diana Hafidah; Masnu'atul Khoiriyah; A. Ansorullah; Dwy Anggara; Khoiriyah (Education Reserach Center, 2026)
This research aims to examine Fazlur Rahman’s thought on Islamic education and to analyze its relevance to the concept of meaningful learning. This study employs a qualitative method with a library research approach. Primary data are derived from Rahman’s major works, such as Islam and Modernity and Major Themes of the Qur’an, while secondary data are drawn from books and journal articles discussing Islamic education and meaningful learning. The data are analyzed using content analysis with a thematic approach. The findings indicate that Rahman emphasizes the integration of revelation and reason, a contextual understanding of Islamic teachings, and the development of moral and intellectual capacities as the primary objectives of Islamic education. These principles strongly correspond to the characteristics of meaningful learning, which stress deep understanding, critical reflection, and the application of knowledge in real-life contexts. This study contributes theoretically by strengthening the philosophical foundation of meaningful learning within Islamic education and contributes practically by proposing a more reflective, contextual, and character oriented paradigm for Islamic Religious Education instruction.